Childhood in world history - Stearns, Peter N., author.
1 online resource.
Keywords: "Now in its fourth edition, Childhood in World History covers the major developments in the history of childhood from the classical civilizations to the present and explores how agricultural and industrial economies have shaped the experiences of children. Through comparative analysis, Peter N. Stearns facilitates a cross-cultural and transnational understanding of attitudes towards the role of children in society, and how "models" of childhood have developed throughout history. He addresses the tension between regional and social/gender differences, on the one hand, and factors that encouraged greater convergence, including the experience of globalization. The book also deals with regional patterns as determined by different religious and cultural systems and family structures. It encourages readers to consider the complexity in evaluating childhood patterns in the past, in light of more modern conditions and expectations, and at the same time to realize some of the problems contemporary children encounter. This updated and expanded fourth edition includes: Broadened discussions of childhood in Asia, Africa, and Latin America Additional text on children's play and the impact of immigration More voices from children throughout Updated bibliographies and suggested readings Concisely presented but broad in scope, this book will be of interest to students of world history and those involved in interdisciplinary approaches to childhood"--